Valve-in-valve transcatheter aortic valve replacement or re-surgical aortic valve replacement in degenerated bioprostheses: a systematic review and meta-analysis of short and mid-term results. (14th October 2021) - Bruno, F; Elia, E; D'Ascenzo, F; Marengo, G; De Filippo, O; Gallone, G; Andreis, A; Fortuni, F; Salizzoni, S; Rinaldi, M; La Torre, M; Conrotto, F; et al.
Abstract: Introduction: Despite limited to short and mid-term outcomes, Valve-in-valve (ViV) transcatheter aortic valve implantation (TAVI) has emerged as a less invasive alternative to redo surgery for high and intermediate-risk patients with good outcomes across different surgical risk profiles. Purpose: The aim of the resent meta-analysis is to compare short and mid-term outcomes of VIV and surgical redo fo patients with a degenerative aortic bioprosthesis. Methods: All studies comparing with multivariate adjustment between ViV TAVI and re-SAVR were screened. All-cause mortality at 30-day and at follow-up were the primary endpoints, while Valve Academy research Consortium (VARC) endpoints at 30 days including stroke, myocardial infarction (MI), major vascular complications, major bleeding, new onset atrial fibrillation (AF) and permanent pacemaker implantation (PPI) during the index hospitalization were the secondary endpoints. Subgroup analysis were performed according to the surgical risk. All the analyses were stratified according to the design of the study (observational vs propensity-matched study). Results: We obtained data from 11 studies, encompassing 8570 patients, 4224 undergoing ViV TAVI and 4346 re-SAVR. Four studies included intermediate-risk patients and seven high-risk patients. Mean age was 76 and 71.5 years in the ViV and re-SAVR group respectively, with a 60.2% and 61.3% of male. For the ViV procedure, BE prostheses were used in the 49.6% of patients and SE prostheses in the 45.8%. The ViV group have higher prevalence of previous CAD (53.8% vs 41.1%) and CABG (35% vs 23.6%) and more history of HF (72.1% vs 65.6%), CKD (26.6% vs 14.8%) and COPD (25.4 vs 14.8%). 30-day all-cause and CV mortality were significantly lower in ViV (OR 0.43, 0.29–0.64 and OR 0.44, 0.26–0.73 respectively), while after a mean follow-up of 717 (180–1825) days, there were no difference between the two groups (OR 1.04, 0.87–1.25 and OR 1.05, 0.78–1.43 respectively). The result were consistent both in intermediate and high-risk classes. The risk of stroke (OR 1.03, 0.59–1.82), MI (OR 0.70, 0.34–1.44), major vascular complications (OR 0.92, 0.50–1.67) and permanent pacemaker implantation (OR 0.67, 0.36–1.25) at 30 days did not differ, while major bleedings and new onset atrial fibrillation were significantly lower in ViV patients (OR 0.41, 0.25–0.67 and OR 0.23, 0.12–0.42 respectively, all CI 95%). Conclusions: In patients with a degenerated aortic bioprosthesis, ViV TAVI is associated with better short-term outcomes, including all-cause mortality, without any difference in all-cause and cardiovascular mortality at mid-term follow-up compared to surgical redo. Funding Acknowledgement: Type of funding sources: None.